The role of time management in the self-organisation of the individual within an effective self-marketing model - L. A. Gladkova; I. V. Gordeev (Вестник университета)
The study determines the role of time management in the self-organisation of a person oriented towards successful career development, identifies opportunities and ways of self-organisation within the effective self-marketing model. Two tests have been conducted among two hundred respondents of the following categories: non-working students, working students, freelancers, specialists, middle managers and top managers. The first testing allowed us to identify differences in the structure of timing during the day by categories of respondents. Based on the second test survey, six base effective time management factors have been analysed: consistency, purposefulness, perseverance, fixation (on structuring activities), self-organisation (through external means), orientation to the present. The results of the study confirm the need for time management, its competent distribution and budgeting, and effective use in the context of the self-organisation unit of the effective self-marketing model.